2022
DOI: 10.1007/s10340-022-01481-9
|View full text |Cite
|
Sign up to set email alerts
|

Lethal, sublethal and transgenerational effects of insecticides labeled for cotton on immature Trichogramma pretiosum

Abstract: The egg parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) regulates lepidopteran pest populations in cotton crops. However, cotton harbors dozens of pests, and growers rely on multiple insecticide applications to manage these damaging organisms. A harmonious integration of control tactics is required for proper pest management, and the use of selective insecticides (i.e., those promoting effective pest control while causing little impact on natural enemies) ts within this scope. This stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…However, the female‐to‐male ratio of F 1 C. maginivantris was significantly decreased when F 0 females were exposed to sublethal concentrations of insecticides. The negative impacts of insecticides on the sex ratio of parasitoids have also been reported previously 34,58,62,63 . Furthermore, the reduction in the female‐to‐male ratio even continued into the F 2 generation, which was indirectly exposed to the insecticides, except for the chlorantraniliprole treatment.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, the female‐to‐male ratio of F 1 C. maginivantris was significantly decreased when F 0 females were exposed to sublethal concentrations of insecticides. The negative impacts of insecticides on the sex ratio of parasitoids have also been reported previously 34,58,62,63 . Furthermore, the reduction in the female‐to‐male ratio even continued into the F 2 generation, which was indirectly exposed to the insecticides, except for the chlorantraniliprole treatment.…”
Section: Discussionsupporting
confidence: 66%
“…The negative impacts of insecticides on the sex ratio of parasitoids have also been reported previously. 34,58,62,63 Furthermore, the reduction in the female-to-male ratio even continued into the F 2 generation, which was indirectly exposed to the insecticides, except for the chlorantraniliprole treatment. Similar transgenerational suppression on the proposition of females has been observed in Trichogramma galloi Zucchi (Hymenoptera:Trichogrammatidae) with six insecticides, including spinosad, 34 and Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) with thiodicarb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Moreover, the assessment of lethal and sublethal effects of insecticides on parasitoids and predators is a center of attention since it has a huge impact on the biological and demographic traits of the bio-agents. 2,[15][16][17][18] The effect can either be stimulating [example: multigenerational sublethal imidacloprid exposure enhanced the fitness traits on Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae) 2 ] or reducing [example: transgenerational exposure to sublethal concentrations of chlorfenapyr, thiodicarb, and flupyradifurone reduced the biological traits of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) 15 ]. In addition, insecticides also intervene in the predator/parasitoid and prey/host interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our results suggest that doses of the four insecticides, at which the vast majority of the exposed wasps survive, compromise the important ecosystem function these insects have as natural enemies as well as their applicability in the context of biocontrol. Although this suggestion is supported by previous studies that have also found sublethal effects of these compounds in parasitic wasps (Costa et al, 2023;Gao et al, 2023;Mohammed & Karut, 2021), further experiments under more realistic semifield conditions are needed for a definitive evaluation.…”
Section: Discussionmentioning
confidence: 80%